2018
DOI: 10.1186/s13024-018-0275-3
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiling of HERV-K(HML-2) in amyotrophic lateral sclerosis and potential implications for expression of HML-2 proteins

Abstract: BackgroundAmyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disorder. About 90% of ALS cases are without a known genetic cause. The human endogenous retrovirus multi-copy HERV-K(HML-2) group was recently reported to potentially contribute to neurodegeneration and disease pathogenesis in ALS because of transcriptional upregulation and toxic effects of HML-2 Envelope (Env) protein. Env and other proteins are encoded by some transcriptionally active HML-2 loci. However, more detailed information is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 90 publications
3
54
1
Order By: Relevance
“…122 Interestingly, ME/CFS and comorbid diseases have been repeatedly associated with stresses of several types, including infections, and reports of altered cytokine profiles are numerous. 16e23,123e125 Thus, it seems plausible that TE aberrant activation is at the core of the molecular mechanisms involved in ME/CFS, a possibility already established for other immune and neurologic diseases such as lupus, 43 multiple sclerosis, 44 or amyotrophic lateral sclerosis 126,127 and yet under explored for ME/CFS. 128,129 In addition, as reviewed in an earlier section, ME/ CFS blood cell genomes present patterns of differential DNA methylation with respect to healthy subjects 28e37,58,71 that might translate into aberrant chromatin topology and abnormal TE transcriptional activation, perhaps leading to element transposition.…”
Section: Genomic Location Associations Between Me/cfs Dna Differentiamentioning
confidence: 99%
See 1 more Smart Citation
“…122 Interestingly, ME/CFS and comorbid diseases have been repeatedly associated with stresses of several types, including infections, and reports of altered cytokine profiles are numerous. 16e23,123e125 Thus, it seems plausible that TE aberrant activation is at the core of the molecular mechanisms involved in ME/CFS, a possibility already established for other immune and neurologic diseases such as lupus, 43 multiple sclerosis, 44 or amyotrophic lateral sclerosis 126,127 and yet under explored for ME/CFS. 128,129 In addition, as reviewed in an earlier section, ME/ CFS blood cell genomes present patterns of differential DNA methylation with respect to healthy subjects 28e37,58,71 that might translate into aberrant chromatin topology and abnormal TE transcriptional activation, perhaps leading to element transposition.…”
Section: Genomic Location Associations Between Me/cfs Dna Differentiamentioning
confidence: 99%
“…We recommend that future ME/ CFS transcriptomic studies avoid RepeatMasker filters to start documenting the potential role of TEs in the disease. In addition, approaches aimed at measuring TE activation impact in ME/CFS such as discriminating microarrays, Northern blot, or RT-qPCR amplifications 126,144,145 should be pursued.…”
Section: April 2019mentioning
confidence: 99%
“…Thus it will be of clear interest to further define the RcREs present in HERV-K mRNAs that are expressed in HIV infected individuals, especially those with strong anti-HERV-K immune responses, and to determine whether the Rev proteins expressed in these individuals can function in conjunction with these RcREs. It has also been reported that the 3q12.3 provirus is actively transcribed in patients with Amyotropic Lateral Sclerosis (ALS) (57) and although this remains controversial, it has been proposed that HERVs plays a pathophysiological role in this lethal disease (for a review see (58). Some HIV-infected patients develop neurological manifestations that resemble classical ALS, although it occurs at a younger age and there has been reports of improvement following the initiation of antiretroviral therapy (59).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence linking retroviruses and HERV-K to ALS includes increased nonspecific reverse transcriptase activity in the blood and cerebrospinal fluid of ALS patients compared to relatives and controls (13)(14)(15)(16), and increased levels of different transcripts of HERV-K in brains of ALS patients compared to controls (17), although not shown in all studies for the gag gene (18). In one study, active loci of HERV-K were found in ALS and HERV-K expression was strongly correlated with TDP-43 expression (19).…”
Section: Introductionmentioning
confidence: 93%